PERAN KEPUASAN KERJA DAN KOMITMEN AFEKSI ANTARA CARING CLIMATE DENGAN KINERJA KARYAWAN - Aginta Chairunnisa Sinulingga; Deasy Aseanty (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
The aim of this research is to exmaining the effects of caring climate, job satisfaction, and affective commitment on job performance in steak restaurant in Tebet, South Jakarta. This study were developed and tested 5 hypotheses, by using Structural Equation Model. Data were collected from 145 employees working on the food, beverage, hygiene, security, service and cashier in steak restaurant in Tebet, South Jakarta. Finding and contribution in this research shown that there is positive and significant effect of caring climate on job satisfaction and affective commitment that effect on job performance. The limitationin in this research was that this study focused only on restaurant as a hospitality industry, only at steak restaurant in Tebet, South Jakarta, and was limited for only four variables.